DESIGN CONCEPTS OF ARTISTIC AND DESIGN IMAGES OF UKRAINIAN HOLIDAYS IN THE LANDSCAPE ENVIRONMENT OF MUSEUM COMPLEXES - Kuzmenko, Anna; Tregub, Nataliia; Kutateladze, Vladyslav (Theory and practice of design, 2025)
Purpose. The purpose of this work is to develop scientifically based concepts for the formation of artistic and design images of Ukrainian festive and educational events in a landscape environment (using the example of the National Literary and Memorial Museum of G.S. Skovoroda). Methodology. The research methodology is based on systemic and environmental approaches, which are focused on the study of complexly organized systems, which include open-air museum complexes. The work uses structural and compositional analysis and synthesis of architectural and design objects in the natural landscape; historical and chronological, visual and analytical, comparative analysis method, typological systematization method, monitoring method, expert subjective assessment method, and experimental design and forecasting method. Results. The following are identified: priority global trends in the field of lighting design of the subject-spatial exterior environment, which are widely used in the practice of Ukrainian lighting designers; types of architectural and landscape LED lighting in the territories of museum complexes are systematized. As a result of the pre-project analysis of the design object, the following were developed: an updated planning solution and functional zoning of the territory of the G.S. Skovoroda museum complex; concepts of light-color complex formation of design objects for the implementation of scenarios of national Ukrainian holidays (Ivana Kupala, Apple Savior) using immersive technologies (virtual reality). A landmark art object was designed – a fountain based on the idea (drawing) of G.S. Skovoroda “Unequal equality for all”. This design concept of artistic and design images in practice, it can be implemented by specialists from Kharkiv enterprises and LEDLIFE LLC, which perform similar tasks in the city of Kharkiv. Scientific novelty. The scientific novelty of the obtained research results lies in the fact that: – for the first time, based on systematized modern world trends in the field of LED technologies, design concepts for the formation of artistic and design images of Ukrainian folk holidays in the landscape environment of the National Literary and Memorial Museum of G.S. Skovoroda have been developed; – the stylistic techniques of LED lighting and the selection of LED equipment in accordance with the theme, symbolism and attributes of Ukrainian folk holidays and festivals have been improved; – the scenario approach to the formation of light and color design objects in the architectural and landscape spaces of museum complexes has been further developed. Practical relevance. The practical significance of the work lies in the possibility of using the obtained theoretical results in the educational process of higher education applicants in the educational and professional programs “Architectural and Landscape Environment” and “Environmental Design”, as well as in the possibility adaptation and implementation of developed design concepts of artistic and figurative solutions for Ukrainian folk holidays in similar Ukrainian open-air museums.